Testicular biometry of Crioula Lageana breed bulls - Cardoso, Cristina Perito (2020)
The purpose of this experiment was to study the testicular biometry of the Crioula Lageana breed bulls. The experiment was developed in Lages, SC, Brazil, where sixty animals with ages between 18 and 144 months were evaluated. The animals were divided in four treatments according to age: Treatment I, animals with 18 months of age;Treatment II, animals between 24 and 36 months of age; Treatment III, animals between 48 and 60 months of age;and Treatment IV, animals with 72 months or more. The researched parameters were: a) scrotal circumference (CE);b) length (CT) and testicular width (LT); c) testicular volume (VT), and d) testicular form. The conclusion is that the Crioula Lageana breed bulls reach their sexual maturity between the ages of 18 and 24 months, and that the parameterslenght, width and volume of the testicles increase until they reach 5 years of age.